GUT MICROBIOTA AND ITS RELATIONS WITH CARDIOVASCULAR RISK FACTORS IN ALMOST HEALTHY INHABITANTS OF MOSCOW AND MOSCOW REGION - D. A. Kashtanova; О. N. Tkacheva; A. S. Popenko; A. V. Tyakht; D. G. Alexeev; Yu. V. Kotovskaya; S. А. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To investigate on the relation of microbiota content  and cardiovascular  risk factors  among  persons  with no  clinical signs  of cardiovascular diseases.Material and methods. In the study, 92 Moscow and Moscow Region inhabitants included, men and women at age 25-76 y.o., with no clinical signs of chronic non-infectious diseases, not taking any medications, but with probable existence of cardiovascular risk factors. All participants underwent prescreening investigation that included physical examination, clinical and biochemical blood collection, electrocardiography,  thread-mill  test,  risk factors  assessment,  and sequencing  of the variable loci V3-V4 of the gene  16S of rRNA of gut microbiota.Results. During the study, it was revealed that in the studied cohort there  were  more  opportunistic  bacteria  in  the  donors  having  risk factors:   Serratia  — in  obese   and  glucose   metabolism  disorder, Prevotella — in obese, disordered  glucose  metabolism  and  raised systolic pressure, Blautia — glucose  metabolism disorder  and raised systolic pressure. Amylolytic bacteria Oscillosipa were less common in obese.Conclusion. The dysbalance   of gut  microbiota  with riased  level of opportunistic  bacteria  that  potentially initiate systemic  non-specific inflammation, is associated with the  existence  of cardiovascular  risk factors.